2008
DOI: 10.1093/jxb/ern143
|View full text |Cite
|
Sign up to set email alerts
|

The human immunodeficiency virus antigen Nef forms protein bodies in leaves of transgenic tobacco when fused to zeolin

Abstract: Protein bodies (PB) are stable polymers naturally formed by certain seed storage proteins within the endoplasmic reticulum (ER). The human immunodeficiency virus negative factor (Nef) protein, a potential antigen for the development of an anti-viral vaccine, is highly unstable when introduced into the plant secretory pathway, probably because of folding defects in the ER environment. The aim of this study was to promote the formation of Nef-containing PB in tobacco (Nicotiana tabacum) leaves by fusing the Nef … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 51 publications
5
70
0
2
Order By: Relevance
“…These results taken together demonstrated that the formation of PBs-like was essential to obtain a 59 higher F1-V accumulation in N. benthamiana leaves. We confirmed the feasibility of using Zera Ò in Nicotiana benthamiana leaves as was previously reported for stable transformed Arabidopsis thaliana (Geli et al 1994) and Nicotiana tabacum leaves (Virgilio et al 2008).…”
Section: Discussionsupporting
confidence: 89%
“…These results taken together demonstrated that the formation of PBs-like was essential to obtain a 59 higher F1-V accumulation in N. benthamiana leaves. We confirmed the feasibility of using Zera Ò in Nicotiana benthamiana leaves as was previously reported for stable transformed Arabidopsis thaliana (Geli et al 1994) and Nicotiana tabacum leaves (Virgilio et al 2008).…”
Section: Discussionsupporting
confidence: 89%
“…These results seem to suggest the existence of a translational negative regulation against zeolin(Cys-) and Dzeolin proteins. The inability to detect Dzeolin is difficult to explain because unstable proteins should be detectable at least at 0-h chase, as shown for ER-localized proteins (de Virgilio et al 2008). One possible explanation is that Dzeolin mRNA translation is very inefficient because of aberrant RNA folding.…”
Section: Production Of Tobacco Transplastomic Plants Expressing Threementioning
confidence: 99%
“…In case of positive results, the next step would be to fuse zeolin with a protein of interest and express this new fusion protein in the chloroplast. This strategy was successfully used in the ER of tobacco leaves to accumulate the human immunodeficiency virus negative factor (Nef) protein, where Nefcontaining PBs were formed by fusing the Nef sequence to zeolin (de Virgilio et al 2008). Zeolin accumulation in the chloroplast upon plastid transformation was on the contrary unsatisfactory, as no zeolin PBs were detected and higher degradation of the recombinant protein was observed with respect to the form expressed in the ER (Bellucci et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, the high number of HIV-1 subtypes and several other factors complicate the design of a successful vaccine (Young et al 2006;Walker and Burton 2008). For such a purpose, various HIV proteins have been expressed in plant cells using either transient or stable transformation (Zhang et al 2000(Zhang et al , 2002Pérez-Filgueira et al 2004;Karasev et al 2005;Obregon et al 2006;Shchelkunov et al 2006;Greco et al 2007;Marusic et al 2007; Barbante et al 2008;de Virgilio et al 2008;McCabe et al 2008;Zhou et al 2008).…”
Section: Introductionmentioning
confidence: 99%